Odpowiedź :
[tex]a)\\\\9x - 2x + 4 = 27\\\\7x+4=27\\\\7x=27-4\\\\7x=23\\\\\\x=\frac{23}{7} \\\\\\b) \\\\2x - x + 6 = -4 + 2x\\\\-x+6=-4\\\\-x=-4-6\\\\-x=-10\\\\\\x=10\\\\\\c)\\\\24 - 6x = 2x - 4x - 12\\\\24-6x=-2x-12\\\\-6x+2x=-12-24\\\\-4x=-36\\\\\\x=9[/tex]
Odpowiedź:
a) 9x - 2x + 4 = 27 / - 4
9x - 2x = 27 - 4
7x = 23 / : 7
x = 23 : 7
x = 23/7
x = 21/7 2/7
x = 3 2/7.
b) 2x - x + 6 = - 4 + 2x / - 2x - 6
2x - x - 2x = - 4 - 6
2x - 3x = - 10
- x = - 10 / × ( - 1 )
x = 10.
c) 24 - 6x = 2x - 4x - 12 / - 24 - 2x + 4x
- 6x - 2x + 4x = - 12 - 24
- 8x + 4x = - 36
- 4x = - 36 / × ( - 1 )
4x = 36 / : 4
x = 9.